Time for action: Science education for an alternative future - Hodson, Derek (International Journal of Science Education, 2003)
Following a brief historical survey of the popular 'slogans' that have influenced science education during the past quarter century and a review of current international debate on scientific literacy and science pedagogy, the author takes the view that while much of value has been achieved, there is still considerable cause for concern and that it is time for action in two senses. First, it is time to take action on the school science curriculum because it no longer meets the needs, interests and aspirations of young citizens. Second, it is time for a science curriculum oriented toward sociopolitical action. The author argues that if current social and environmental problems are to be solved, we need a generation of scientifically and politically literate citizens who are not content with the role of 'armchair critic'. A particular concern in North America is the link between science education, economic globalization, increasing production and unlimited expansion - a link that threatens the freedom of individuals, the spiritual well-being of particular societies and the very future of the planet. The author's response is to advocate a politicized, issues-based curriculum focused on seven areas of concern (human health; food and agriculture; land, water and mineral resources; energy resources and consumption; industry; information transfer and transportation; ethics and social responsibility) and addressed at four levels of sophistication, culminating in preparation for sociopolitical action. The curriculum proposal outlined in the article is intended to produce activists: people who will fight for what is right, good and just; people who will work to re-fashion society along more socially-just lines; people who will work vigorously in the best interests of the biosphere. At the heart of this curriculum is a commitment to pursue a fundamental realignment of the values underpinning Western industrialized society. Achieving that goal is a formidable task - one that will not be achieved by conventional approaches to curriculum development and teacher education. The author's solution is action research linked to community involvement.